EXPLORATION AND IDENTIFICATION OF SUCCESS FACTORS OF CATTLE POPULATION INCREASE PROGRAM - Rini Mastuti; Muhammad Fuad; Supristiwendi Supristiwendi; Hanisah Hanisah; Muhammad Jamil (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
The Langsa City area is one of the 9 implementation areas of the Beef Self-Sufficiency Program (PSDS) in Aceh Province. The implementation of this activity is supported by the Upsus SIWAB Program which requires cows to be mated and uses the latest Indonesian Animal Health Information System (iSIKHNAS). This study aims to investigate and identify the factors that exist in Langsa City, Aceh Province, Indonesia. To achieve this, data was collected through surveys, field observations and in-depth interviews with key respondents and 100 farmers, using questionnaires, tape recorders, and image documentation. The focus is on identifying PSDS leveraging factors, with the object of study related to breeders, inseminators, livestock, and supporting factors. Furthermore, the data collected was carried out quantitatively using Structural Equation Modeling Partial Least Square (SEM-PLS) data analysis, and qualitatively using descriptive methods. The results showed that the condition of the livestock which was influenced by the characteristics of breeders and inseminators became a key factor in Langsa City, Aceh Province at this time. Considering these results, recommendations are made to the government to design better PSDS policies in the future.